Distinct microbial community structures formed on the biofilms of PLA and PP, influenced by physicochemical factors of sediment and polymer types in a 60-day indoor study - Jiao, Yiying; Zhou, Anqi; Zhang, Delang; Chen, Mo; Wan, Liang (Frontiers in Environmental Science, 2024)
Microplastics (MPs) are colonized by biofilm-forming microbes. Biodegradable plastics, popular replacements for traditional plastics, still have unknown biofilm formation characteristics. We conducted a 60-day indoor experiment, where sediment was exposed to traditional MPs (polypropylene, PP), biodegradable MPs (polylactic acid, PLA), and glass beads (GLASS). The microbial communities in the MPs-biofilm were analyzed using high-throughput sequencing. Results indicated that Proteobacteria was the dominant phylum on all substrates, followed by Actinobacteria, and Firmicutes.At the genus level, the majority of microorganisms colonizing PP possessed nitrification and denitrification capabilities, while the dominant bacteria on PLA were capable of degrading lignin, cellulose and carbon metabolism. The genus Sphingomonas, a promising bacteria capable of degrading biodegradable microplastics, was particularly discovered on the PLA biofilm, meanwhile, bacterial colonization of PLA indirectly increased the potential for human transmission of pathogens.Redundancy analysis revealed that the pH and moisture significantly affected the bacterial communities. Pearson correlation heatmap indicated that the abundance of the majority of dominant bacterial genera of two MPs biofilms is negatively correlated with the physicochemical parameters of sediment (pH, moisture, TN, TP), except for salinity.The microbial communities associated with PP and PLA exhibited distinct differences caused by the combined effects of changes in physicochemical properties of sediment and different material substrates. This study provides further evidence of the significant selective features exhibited by microbial colonization on these two MPs when exposed to the same source community, offering insights into the exploration of promising bacteria for MPs degradation.